Present and Future Changes in Land‐Atmosphere Coupling of Water and Energy Over Extratropical Forest Regions. Issue 8 (14th April 2023) - Zhu, Qing; Riley, William; Tang, Jinyun; Burrows, Susannah; Harrop, Bryce; Shi, Xiaoying; Yang, Xiaojuan; Maltrud, Mathew; Calvin, Katherine
Abstract: Couplings between land and the near surface atmosphere are modulated by interactions between soil conditions, vegetation dynamics, turbulent fluxes, and atmospheric properties. How the land‐atmosphere coupling responds to warming and elevated CO2 are important for understanding the land surface carbon, energy, and water cycles. In this work, we documented this coupled land‐atmosphere network based on observations and the Energy Exascale Earth System Model (E3SM) simulations over extratropical forest ecosystems. We employed a transfer entropy approach and novel network metrics to reveal patterns and strength of the land‐atmosphere coupling under historical conditions and a future high emission scenario (SSP585). We found that, in observations, the present‐day extratropical forest coupling network has high network connectivity (72%–88% of the targeted processes are coupled). E3SM reasonably captured the extratropical forest coupling network (modeled network connectivity was 81%–96%) and predicted that the coupling strength would significantly increase by 28% (±3%) under warming and elevated CO2 conditions. Furthermore, E3SM factorial coupled experiments suggested that warming enhanced soil nitrogen mineralization favoring plant nitrogen uptake and vegetation growth were responsible for the strengthening future land‐atmosphere coupling. This work provides new metrics to analyze and document complex couplings for coupled earth system processes and highlights the important roles soil nutrient availability and biogeochemistry have on land‐atmosphere coupling. Plain Language Summary: Land exchanges a vast amount of water and energy with atmosphere that drive the coupling of atmosphere conditions (e.g., temperature), vegetation activities (e.g., growth), and soil properties (e.g., soil moisture). However, such land‐atmosphere coupling is likely modified due to climate warming and rising atmospheric CO2 concentrations in the future. This work used observational datasets and coupled earth system model experiments to address the important questions of how and why the land atmosphere coupling change over time. We found strong evidence that elevated CO2 concentrations could dampen while warming would largely enhance the land‐atmosphere coupling strength, leading to a net increase of land‐atmosphere coupling until the end of 21st century under the SSP585 high emission scenario. Key Points: Using novel network metrics, we found high connectivity of land‐atmosphere coupling of water and energy over extratropical forest regions Energy Exascale Earth System Model coupled experiments revealed that the land‐atmosphere coupling strength would increase by 28% under SSP585 high emission scenario